Infant Exposure to Dolutegravir Through Placental and Breast Milk Transfer: A Population Pharmacokinetic Analysis of DolPHIN-1. (21st December 2020) - Dickinson, Laura; Walimbwa, Stephen; Singh, Yashna; Kaboggoza, Julian; Kintu, Kenneth; Sihlangu, Mary; Coombs, Julie-Anne; Malaba, Thokozile R; Byamugisha, Josaphat; Pertinez, Henry; Amara, Alieu; Gini, Joshua; et al.
Abstract: Background: Rapid reduction in human immunodeficiency virus (HIV) load is paramount to prevent peripartum transmission in women diagnosed late in pregnancy. We investigated dolutegravir population pharmacokinetics in maternal plasma, umbilical cord, breast milk, and infant plasma samples from DolPHIN-1 participants (NCT02245022) presenting with untreated HIV late in pregnancy (28–36 weeks gestation). Methods: Pregnant women from Uganda and South Africa were randomized (1:1) to daily dolutegravir (50 mg/d) or efavirenz-based therapy. Dolutegravir pharmacokinetic sampling (0–24 hours) was undertaken 14 days after treatment initiation and within 1–3 weeks after delivery, with matched maternal and cord samples at delivery. Mothers were switched to efavirenz, and maternal and infant plasma and breast milk samples were obtained 24, 48, or 72 hours after the switch. Nonlinear mixed-effects modeling was used to describe dolutegravir in all matrices and to evaluate covariates. Results: A total of 28 women and 22 infants were included. Maternal dolutegravir was described by a 2-compartment model linked to a fetal and breast milk compartment. Cord and breast milk to maternal plasma ratios were 1.279 (1.209–1.281) and 0.033 (0.021–0.050), respectively. Infant dolutegravir was described by breast milk–to–infant and infant elimination rate constants. No covariate effects were observed. The median predicted infant dolutegravir half-life and median time to protein-adjusted 90% inhibitory concentration (0.064 mg/L) for those above this threshold were 37.9 (range, 22.1–63.5) hours and 108.9 (18.6–129.6) hours (4.5 [0.8–5.4] days) (n = 13), respectively. Conclusions: Breastfeeding contributed relatively little to infant plasma exposure, but a median of 4.5 days of additional prophylaxis to some of the breastfed infants was observed after cessation of maternal dolutegravir (3–15 days postpartum), which waned with time postpartum as transplacental dolutegravir cleared. Abstract : The population pharmacokinetic model described dolutegravir in maternal and infant plasma and transplacental and breastmilk passage. Based on infant elimination profiles, dolutegravir provided a median of 4.5 days prophylactic coverage to breastfed infants following maternal drug cessation 3-15 days postpartum.